ANALISIS BAHAN AJAR FASE A MATEMATIKA KELAS 1 DI SD NEGERI 4 TIGA: BAHAN AJAR - I Putu Oka Suardana; Ratna Indra yanti (Jurnal Pendidikan Dasar Rare Pustaka, 2026)
The aim of this research is to analyze teaching materials for Grade 1 Mathematics Phase A and recommend teaching materials that are more effective in increasing students' understanding of Mathematics Lessons. This type of research is qualitative descriptive research. Data collection techniques used observation and interviews with teachers and students at SD N 2 Sulahan. The research results show that first, teaching materials help teachers adapt learning materials to students' needs, in the form of video books, digital (internet-based), games and so on to stimulate students' interest in learning. Second, teaching materials are very important for student success, namely materials that can answer problems to achieve learning and must meet the criteria of being valid, practical and effective. Third, there are several ways to create interactive and interesting teaching materials, namely using images and videos, creating animations and simulations, creating educational games, utilizing available technology. For example, in the process of developing teaching materials using Microsoft Powerpoint software, it is very helpful to create more interesting materials. , efficient, practical and effective in conveying information, especially in phase a subjects of class 1 Pancasila education. Fourth, games and videos are a fun and effective method for students. For example, in Phase A Mathematics lessons, animated videos can visualize lesson material such as integers, present visual displays of subtraction and addition of integers in the form of interesting and easy-to-remember stories, making it easier for students to understand and remember the lesson material.